Ventriculo-gallbladder shunt: a case report of a neglected technique - Valdecir Spenazato; Aline Rabelo Rodrigues; Beatriz Pereira Vilela; Carolina Barcha Santos; João Victor Carvalho da Paz; Ricardo Santos de Oliveira; Matheus Fernando Manzolli Ballestero (Brazilian Society for Pediatric Neurosurgery, 2022)
Hydrocephalus is a common central nervous system (CNS) disorder in which there is an excess of cerebrospinal fluid within the cerebral ventricles, leading to their dilation. There are several pathologies that lead to this scenario: cerebral aqueduct stenosis, congenital malformations, cerebral neoplasms, cerebral hemorrhages, traumatic brain injury and meningitis, while the signs and symptoms differ according to age, underlying disease, malformations or associated injuries, and intracranial pressure level. The invasive treatment routinely performed for hydrocephalus is the insertion of a drainage system, known as a bypass. The present report describe a case of a 4-year-old patient with a history of using multiple ventricular shunts with multiple complications which had as a definitive treatment a ventriculogallbladder shunt (VGB) technique, and was asymptomatic after 2 years of follow-up. VGB has a great indication factor, does not present physiological changes due to its absorption of CSF, manifests fewer complications during its use, and is controlled by radiography and USG. However, it is currently used in cases of ventriculoperitoneal shunt  (VP) failure. A VGB placement carries the same risk of all inherent complications that can occur with a VP, including malfunction and infection. It can be concluded that a VGB is underestimated by most physicians as it is not a conventional method. Despite this, it should be an alternative to be considered in case of refractory patients and in the absence of effectiveness of other types of shunts.